The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1348/096317904x23790
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of a preventive job search program on re‐employment and mental health at 2‐year follow‐up

Abstract: This study investigated whether a preventive, group‐based job search program has long‐term beneficial effects on the re‐employment and mental health of participants who have been unemployed for a prolonged period of time. A total of 1,227 unemployed Finnish job seekers participated in this randomly assigned experimental field study. Participation in the programme significantly decreased symptoms of depression, and increased the self‐esteem of the participants during the 2 years of follow‐up. Compared to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 27 publications
4
69
0
4
Order By: Relevance
“…At the two-year follow-up, significantly more of the experimental group were re-employed, in subsidised work or in vocational training (70.4%) than the control group (64.1%). The experimental group also reported significantly decreased depressive symptoms and increased self-esteem in comparison with the controls (Vuori & Silvonen, 2005).…”
Section: Previous Studies Of the Jobs Programmementioning
confidence: 74%
See 1 more Smart Citation
“…At the two-year follow-up, significantly more of the experimental group were re-employed, in subsidised work or in vocational training (70.4%) than the control group (64.1%). The experimental group also reported significantly decreased depressive symptoms and increased self-esteem in comparison with the controls (Vuori & Silvonen, 2005).…”
Section: Previous Studies Of the Jobs Programmementioning
confidence: 74%
“…The Työhön Job Search Programme is a Finnish version of the JOBS programme (Vuori et al, 2002;Vuori & Silvonen, 2005) which examined the programme in the context of a European labour market for individuals who had been unemployed for a longer period (mean = 10.7 months). At the two-year follow-up, significantly more of the experimental group were re-employed, in subsidised work or in vocational training (70.4%) than the control group (64.1%).…”
Section: Previous Studies Of the Jobs Programmementioning
confidence: 99%
“…The Työhön Job Search Program is almost identical to the 20-hr MPRC program but includes some minor adaptations. The Työ-hön program showed beneficial effects similar to those of the U.S. MPRC Job Search Program and demonstrated that the intervention program is also beneficial to longer term unemployed workers (Vuori & Silvonen, 2005;Vuori et al, 2002). A study by Vuori and Vinokur (2005) demonstrated this mediating role of job-search self-efficacy and inoculation against setbacks for mental health and reemployment outcomes.…”
mentioning
confidence: 85%
“…Finnish long-term unemployed individuals, who participated to such a shortterm subsidized job, had a better chance of getting reemployed than those who did not have a subsidized job (Santamäki-Vuori 1996). These interventions were found to be effective in the protection of psychological well-being and were most beneficial for the group of unemployed with the poorest mental health (Machin and Creed 2003;Vuori and Silvonen 2005). The protective mechanism behind these intervention strategies can be understood with reference to the latent deprivation model of Jahoda (1982) as they satisfy both manifest (i.e.…”
Section: Implications For Practicementioning
confidence: 99%